2013
DOI: 10.1182/blood-2012-07-379016
|View full text |Cite
|
Sign up to set email alerts
|

How I treat older patients with ALL

Abstract: The treatment of older patients with acute lymphoblastic leukemia (ALL) is an unmet medical need. In Western countries, the population is aging, which means there will be an increasing number of older patients. However, in the past few decades, there has been little improvement in treating them, and few clinical trials specifically designed for older patients with ALL have been reported. Older patients with ALL have a significantly lower complete response rate, higher early mortality, higher relapse rate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 80 publications
0
75
0
2
Order By: Relevance
“…MRD after induction therapy is regarded as an independent predictor for survival in younger adults with ALL [32,33] and seems to be a powerful predictor for outcome in older adults [4]. Furthermore, Bassan and colleagues previously demonstrated that MRD status can assist in allocating adult patients in remission to maintenance or HSCT [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRD after induction therapy is regarded as an independent predictor for survival in younger adults with ALL [32,33] and seems to be a powerful predictor for outcome in older adults [4]. Furthermore, Bassan and colleagues previously demonstrated that MRD status can assist in allocating adult patients in remission to maintenance or HSCT [34].…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2; P value nonsignificant for both comparisons). The 3-year CIR and NRM were 61% [41-76] and 9% [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] for the chemotherapy-only group and 28% and 32% for the transplant group (Table II; Fig. 3; P 5 0.011 for CIR and P 5 0.014 for NRM).…”
Section: Chemotherapy Vs Allogeneic Transplantation In First Remissionmentioning
confidence: 99%
See 1 more Smart Citation
“…These likely evolve over time and/or differ with phases of treatment, so tracking the progression of the sample over time would be important. Two key questions arise: (1) what is the patient's process; and (2) when do they decide. The answers guide the presentation of information by the HCT team and may inform novel solutions to improve the current system.…”
Section: Hct In Oldermentioning
confidence: 99%
“…[1][2][3][4][5] For these cancers, treatment options that can be used to prolong their lives include allogeneic hematopoietic cell transplantation (alloHCT). AlloHCT may be the only curative option and its associated risks of significant morbidity and mortality warrant a clear, informed decision-making process.…”
Section: Introductionmentioning
confidence: 99%